Greek Material Clothed in Islamic Garb: Ḥunayn Ibn ‘Isḥāq’s Fī Manāfi’ al-’Adā’ - Göksu, Ahmet; Al-Khaffaf, Ebrahim (Fatih Sultan Mehmet Vakıf Üniversitesi, 2024)
The Greek version of Claudius Galen’s On the Usefulness of the Parts [Περὶ χρησέως μορίων: Peri chrēséōs moríōn], an important book in terms of both the history of medicine and theology, has survived to this day. This work by Galen was translated into Arabic under the name Fī Manāfi’ al-’Adā’ by Ḥunayn Ibn ‘Isḥāq in Baghdad in the 9th century during the translation movement in the Islamic civilization. This article aims to observe the changes Ḥunayn made in the text by generally focusing on specific terms and phrases. Particularly, this will be achieved by comparing the English translation of Galen’s Greek original work with its Arabic translation. And this will be specifically accomplished by drawing attention to Ḥunayn’s method and approach of translation in adapting Galen’s work On the Usefulness of the Parts to Islamic culture. It is clear that the term “Islamic culture” encompasses a vast array of concepts. However, for the purposes of this article, our focus will be on Islam’s robust monotheistic principles, its rejection of pagan notions, and the unique phrases that can be traced back to the Qur’ān. Elvira Wakelnig described this translation approach as a method wherein the “Greek material was clothed in Islamic garb”. The reason for choosing this particular book stems from the fact that its topic is closely related to rational theology and it has arrived to us in a complete form in both its original Greek language as well as in its Arabic translation made by Ḥunayn.

Claudius Galen’in Organların İşlevleri Üzerine [Περὶ χρησέως μορίων: Peri chrēséōs moríōn] adlı eseri, hem tıp hem de teoloji tarihi açısından önemli bir kitaptır ve Yunancası da günümüze ulaşmış bir eserdir. Galen’in bu eseri İslam medeniyetinde tercüme hareketi içinde 9.yy.da Bağdat’ta Huneyn b. İshak tarafından Fi Menâfi’ul ‘Azâ adıyla Arapçaya çevrilmiştir. Bu çalışmada, hem Yunanca eserin İngilizce tercümesi hem de Arapça tercümesi karşılaştırılarak, genel olarak belirli terim ve ifadelere odaklanarak Huneyn’in metinde yaptığı değişiklikleri gözlemlemeyi amaçlamaktadır. Amacımız, tercüme metinleri karşılaştırırak Huneyn b. İshak’ın Galen’in eserinin Arapça alımlanışında İslam dini ve kültürü ile kurduğu ilişkiyi incelemektir. Kuşkusuz, “İslam dini ve kültürü” geniş bir kavram yelpazesini kapsar, ancak bu makalenin kapsamı içinde odaklandığımız nokta İslam’ın merkezinde yer alan tektanrıcılık prensipleri, putperest düşüncelere karşı reddiye ve Kuran’da izini sürebileceğimiz ve bulabileceğimiz özgün ifadelerdir. Elvira Wakelnig bu çeviri yaklaşımını “İslam kisvesine bürünmüş Yunanca malzeme” olarak tanımlar. Bu makale de başlığını Wakelnig’in bu veciz terkibinden almakta ve Huneyn’in Fi Menâfi’ul ‘Azâ adlı çevirisini bu yaklaşımla incelemektedir. Bu eseri seçmemizin nedeni, konusunu rasyonel teolojiye yakın olan bu kitabın hem orijinal dili olan Yunanca hem de Huneyn tarafından tercüme edilen Arapça tercümesiyle eksiksiz bir şekilde elimize ulaşmasıdır.
İslami Kisveye Bürünmüş Yunanca Malzeme: Huneyn b. İshak’ın Fi Menâfi’ul ‘Azâ Adlı Eseri
Keywords: Galen; Hunayn Ibn Ishaq; Translation Movement; Arabic Reception; on The Usefulness of The Parts; Huneyn b. İshak; Çeviri Hareketi; Arapça Alımlanış; Organların İşlevleri Üzerine